Pengembangan Game Maze Berbantu Program Scratch Untuk Meningkatkan Kemampuan Pemecahan Masalah Anak usia 5-6 Tahun - Permatasari, Lily (Prosiding University Research Colloquium, 2021)
In this study, a "maze game" was developed as a medium to stimulate problem solving abilities of children aged 5-6 years. This study aims to describe the development process, feasibility, and effectiveness of game maze as a medium for stimulating problem solving abilities of children aged 5-6 years. The maze game development model refers to the ADDIE development model with the following stages: 1) analysis, 2) design, 3) development, 4) implementation and 5) evaluation. The results of this study indicate that Maze Game was made with Scratch 3.0 software consists of 16 levels with tiered difficulty levels. Maze Game can be run on a computer or laptop with a windows operating system. Maze Game was declared suitable for use based on the results of the assessment of the quality of the games tested on media experts which could be categorized as very feasible with a feasibility percentage of 80.26%, Material test assessments on material experts obtained very decent results with a feasibility percentage of 77.94%, and practitioner assessments were categorized as very feasible with a feasibility percentage of 88.24%. The results of the analysis show that the use of maze games is effective in improving problem solving abilities of children aged 5-6 years.